Mindfulness-based Art Therapy Activities (MBAT) As a Way to Reduce Anxiety in Young Adults - Fuentes, Fiorella Ingrid Luna (University of Wisconsin-Superior, 2019)
According to the DSM-V (2013), Anxiety Disorders are those that are characterized by features of excessive fear and anxiety that are related to behavioral disturbances (p.189). Studies have shown that this disorder is among the most common in the US, and it affects people of all ages indistinctly. As a consequence, there are many available treatment options; however, it has been proven that mindfulness-based Art therapy activities can help in reducing anxiety, stress and improving the quality of life on patients that decide to try it. The mindful awareness that art can cultivate and the engagement in the present moment offers the patients the opportunity to be an external observer and, at the same time, an internal part of the experience. Consequently, the aim of this paper is to prove the positive effects of Mindfulness-based Art Therapy Activities (MBAT) in reducing anxiety features in young adults attending college.
Keywords: Anxiety; Behavioral Disturbances; Mindfulness; Art therapy; Mindfulness-based Art Therapy Activities (MBAT)